Merapi ceria alert: Early childhood education in disaster-prone areas of Mount Merapi - Alan Kusuma; Audia Ananda Saputri; Jihan Ika Ayuningtyas; Dwi Susanti; Fadillah Sandy; Annis Azhar Suryaningtyas (Universitas Muhammadiyah Magelang, 2025)
Dukun Village, Magelang Regency, Central Java, lies within Mount Merapi's eruption-prone zone, necessitating effective disaster preparedness education, especially for vulnerable children. This community service project aimed to provide disaster mitigation education to KB Insan Mulia II children. The project involved preparation, implementation, and evaluation stages. The